2005
DOI: 10.1177/0115426505020002218
|View full text |Cite
|
Sign up to set email alerts
|

Levocarnitine and Dialysis: A Review

Abstract: Among the various metabolic abnormalities documented in dialysis patients are abnormalities related to the metabolism of fatty acids. Aberrant fatty-acid metabolism has been associated with the promotion of free-radical production, insulin resistance, and cellular apoptosis. These processes have been identified as important contributors to the morbidity experienced by dialysis patients. There is evidence that levocarnitine supplementation can modify the deleterious effects of defective fatty-acid metabolism. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 153 publications
0
42
0
Order By: Relevance
“…Despite many trials, the results regarding the effects of L -carnitine supplementation on cardiac function of chronic hemodialysis patients are controversial [8,9,10,11]. Some authors noted an improvement [13,14,15,16,17], while others found no change [18,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite many trials, the results regarding the effects of L -carnitine supplementation on cardiac function of chronic hemodialysis patients are controversial [8,9,10,11]. Some authors noted an improvement [13,14,15,16,17], while others found no change [18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an improvement in cardiac function of patients with chronic hemodialysis associated with carnitine therapy might be expected. However, the results of previous studies are conflicting [8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration of LC of chronic hemodialyzed patients in plasma and tissues decreased because of the impaired synthesis in kidney and liver and the great loss across the dialysis membrane during hemodialysis [3,4,5]. …”
Section: Introductionmentioning
confidence: 99%